Systematic literature review: Curriculum development principle - Amanda Azalia; Deswa Putri Lerian; Erwin Taufik; Sarah Nurul Izzah; Surya Nugraha; Ghaitsa Zahira Arya (Universitas Pendidikan Indonesia, 2023)
Curriculum development is significant to do. The curriculum is the core of the essential educational process carried out in various schools. Indonesia has undergone several changes to the newest curriculum, namely the independent curriculum. Changes in the education curriculum must adapt to the times without leaving the relevant cultural values of society. The method used in this study is a literature study through sources related to the principles of curriculum development. Curriculum development sources include; empirical data, experimental data, folklore, and general community knowledge. The directions in curriculum development are divided into two things: (1) General Principles, which include; the principle of relevance, the principle of flexibility, the principle of continuity, the principle of practicality, and the principle of effectiveness, (2) Specific Principles include; principles of determining educational goals, selecting educational content, selecting teaching and learning processes, selecting media and teaching tools, and principles relating to assessment. The curriculum plays a vital role in determining the success of education because the existence of the curriculum is concrete evidence in trying to achieve national education goals.